Dečko koji obećava . The Promising Boy - Radivojević, Miloš Miša (Avala Film Beograd, 1981)
The beginning of the movie finds Slobodan Milošević, a promising medical student from a respectable family background, being seduced by an open-minded Swiss girl. When he confesses the affair to his long-term girlfriend Maša, she hits him on the head with a paddle and his behavior is radically changed. He leaves home, has a serious quarrel with his parents, quits the university and engages in a series of sexual encounters with unknown women, including Maša’s mother. All of a sudden Slobodan's life evolves in the world without any social or moral obligations. Soon, he makes new friends in the Belgrade rock scene and forms a successful band, once again, with a promising, though different future in front of him. In the meanwhile, Maša, offended by his behavior, believes that another blow in the head would put things back under control again. This does indeed happen when Slobodan is injured in a bike crash: once he wakes up in hospital, he indeed starts acting “normal” again. He even plans a wedding with Maša only to find out, in the middle of the ceremony, that Pit, his friend from the band, has died and in his final agony he beats his head against the mirror.